Exceptional interfacial solar evaporation via heteromorphic PTFE/CNT hollow fiber arrays. Issue 1 (14th December 2020) - Li, Tiantian; Fang, Qile; Wang, Jianqiang; Lin, Haibo; Han, Qiu; Wang, Peng; Liu, Fu
Abstract : An extra energy field from the absorptive base is created, and 360° evaporation is achieved by a versatile heteromorphic array configuration. Abstract : Interfacial solar vapor generation demonstrates great potential for water purification. To facilitate water evaporation processes, materials with high solar-thermal efficiency and low thermal loss are developed. Herein, a heteromorphic arch-like evaporator is presented for exceptional solar-to-steam conversion by designing a versatile heteromorphic array configuration of polytetrafluoroethylene (PTFE) hollow fibers decorated with carbon nanotubes (CNT). The arch-like fiber array achieves a 360° evaporation and generates extra thermal energy from the absorptive base (carbon cloth, PS foam and PVDF membrane) by manipulating a fiber array pattern (compact, staircase and spaced). An indoor evaporation rate of 2.15 kg m −2 h −1 and outdoor freshwater reclamation of 10–16 kg m −2 per day can be obtained with multiple fiber staircase arrays using carbon cloth as the base under one sun illumination.